ELIZABETH H. DOW, Archivists, Collectors, Dealers, and Replevin: Case Studies on Private Ownership of Public Documents - Belton, Tom (Archivaria, 2013)
Archivists, Collectors, Dealers, and Replevin: Case Studies on Private Ownership of Public Documents. ELIZABETH H. DOW. Lanham, MD: Scarecrow Press, 2012. xvi, 128 pp. ISBN 978-0-8108-8377-2.